1996
DOI: 10.2500/105065896781795184
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Active Anterior and Posterior Rhinomanometry in British Adults

Abstract: In this study, active Anterior Rhinomanometry (ARM) and Posterior Rhinomanometry (PRM) were performed sequentially by 56 normal British Caucasian adults using an on-line Mercury Electronics NR6D Rhinomanometer. Xylometazoline nasal spray was used as a nasal decongestant before the test. In addition, repeated measurements were made on a randomly selected 13 subjects to evaluate the error of the methods. The mean total nasal airway resistance by the anterior method was found to be 0.182 Pa/cm3/s at a reference p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In other studies, failure rates have ranged from 8% (in well-trained individuals) [15] to 50% (in children) [16]. In a recent study by CANBAY et al [2], nine of 56 (16%) subjects did not complete the PRM recordings satisfactorily and were therefore excluded from the study. Interestingly, the same group who reported a failure rate of 15% with conventional PRM suggested that a plethysmograph be used for recording flow in order to leave free access to the face and therefore to obtain better control of the position of the oral tube; with this technique, the failure rate was as low as 1.4% in 1,000 paediatric patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, failure rates have ranged from 8% (in well-trained individuals) [15] to 50% (in children) [16]. In a recent study by CANBAY et al [2], nine of 56 (16%) subjects did not complete the PRM recordings satisfactorily and were therefore excluded from the study. Interestingly, the same group who reported a failure rate of 15% with conventional PRM suggested that a plethysmograph be used for recording flow in order to leave free access to the face and therefore to obtain better control of the position of the oral tube; with this technique, the failure rate was as low as 1.4% in 1,000 paediatric patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…The Rhinomanometer 300 (Atmos, Lenzkirch, Germany) was used in the study. During rhinomanometric measuring, the patients performed polite yawning technique and the technique applied did not differ greatly from the standard technique 6,7 . The measurements were used to evaluate the effect of polite yawning technique on nasal airflow rate.…”
Section: Methodsmentioning
confidence: 99%
“…In a first ever study, Stocks and Godfrey (1978) demonstrated a greater nasal resistance in caucasian than in black infants during the first year of life. 8 Babatola (1990)9 studied resistance in Nigerian blacks, but did not find it to be significantly different from the caucasian values provided in the literature. A similar negative result was obtained by Calhoun et al (1990) in their measurement of whites, blacks, and hispanics.…”
mentioning
confidence: 85%
“…A detailed description of the method and the evaluation of its errors have been presented previously. 8 Means and standard deviations of the nasal resistance values were calculated for the caucasians and blacks separately for both anterior and posterior methods. The means of the two groups were compared with an uncorrelated t-test.…”
Section: Measurement Of Nasal Resistancementioning
confidence: 99%